2009
DOI: 10.1097/sla.0b013e31819ed958
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Volume Impacts Hospital Mortality for Pancreatic Resection

Abstract: After controlling for patient demographics and factors, pancreatic resection by a HV surgeon in this case-controlled cohort was independently associated with a 51% reduction in in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 33 publications
3
82
0
5
Order By: Relevance
“…There are many surgeon‐specific factors that affect post‐operative morbidity, such as age, gender, extent and type of training and operative volume or workload. Higher surgeon volumes in pancreatic surgery have been linked to an overall improvement in patient outcomes, including reduced intraoperative blood loss, shorter hospital stay, lower pancreas fistula rate and improved mortality 1, 9. However, Waljee et al 14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many surgeon‐specific factors that affect post‐operative morbidity, such as age, gender, extent and type of training and operative volume or workload. Higher surgeon volumes in pancreatic surgery have been linked to an overall improvement in patient outcomes, including reduced intraoperative blood loss, shorter hospital stay, lower pancreas fistula rate and improved mortality 1, 9. However, Waljee et al 14.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally reported that the incidence of clinically relevant post‐operative pancreatic fistulas after PD is 7.6–36.4%,1, 2, 3, 4, 5 in accordance to the definition of the International Study Group of Pancreatic Fistula (ISGPF) 6. Researchers have suggested factors that affect pancreatic leakage after PD, including male gender, advanced age, post‐operative albumin level, intraoperative bleeding, soft pancreatic parenchyma, small pancreatic duct, drain amylase level on post‐operative day one, pancreatic parenchymal thickness and surgeon volume, among others 1, 7, 8, 9, 10, 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…impacto del volumen por cirujano en la mortalidad hospitalaria La presencia de tasas de mortalidad operatoria menores en los centros de alto volumen después de la resección pancreática [3][4][5][6][7][8]15,16 ha planteado también el impacto del volumen cirujano en la mortalidad.…”
Section: Pancreatoduodenectomíaunclassified
“…High hospital volume is strongly correlated with low mortality rates (17). Furthermore, a high volume surgeon is associated with low mortality rates after pancreatic resections (18,19). In is worth to mention however that even nowadays the mortality after pancreatectomies is not nil, particularly after pancreatico-duodenectomies.…”
Section: Resectable Pdacmentioning
confidence: 99%